Heavy non-aqueous phase pollutant self-recognition repair material as well as preparation method and application thereof
By developing a self-identification repair material with multiple core-shell structures, using modified zero-valent iron, electron shuttle and biostimulatory materials, combined with deoxidants and fat-soluble materials, the problems of tail rebound and low drug utilization in DNAPL pollutant treatment were solved, and efficient pollutant removal and drug utilization were achieved.
Patent Information
- Application Number
- CN202311372091.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-20
AI Technical Summary
The prior art has problems of tail rebound and low drug utilization when dealing with DNAPL contaminants, and lacks efficient identification and selective materials.
It provides a heavy non-aqueous phase pollutant self-identification repair material, with a multi-core-shell structure, the inner core contains modified zero-valent iron, electron shuttle and biostimulating material, the intermediate layer contains deoxidant, and the coating layer contains fat-soluble material. This material initiates the release of agent through the autolysis mechanism of the coating layer, achieving efficient purification and removal of the DNAPL phase.
The selective recognition and efficient purification and removal of DNAPL phase are achieved, which improves the effective utilization of the agent and protects the internal agent materials from oxidation.
Smart Images

Figure CN119858971A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of site organic pollutant remediation, and in particular to a site heavy non-aqueous phase pollutant self-identification remediation material, a preparation method and application thereof. Background Art
[0002] A large number of raw materials and products in the petrochemical, fine chemical, printing and dyeing, pharmaceutical and other industries enter the natural environment during production, storage and transportation, causing varying degrees of pollution to the soil and groundwater. Among them, organic solvents represented by chlorinated hydrocarbons and polychlorinated biphenyls are persistent pollutants. Organic matter containing one or more chlorine atoms has a density greater than groundwater and a low solubility. It also has the characteristics of low viscosity and "three-cause" toxicity. It is called heavy non-aqueous phase pollutants (DNAPL), which can penetrate the unsaturated and saturated zones and remain at the bottom of the aquifer. Affected by the groundwater flow rate and medium heterogeneity, the DNAPL phase pollutants of chlorinated hydrocarbons migrate and diffuse to form a pollution plume, becoming an important risk hazard to the lives and health of people in the plant and surrounding areas. Therefore, in view of the difficulties of low utilization rate and poor accuracy of DNAPL pollution control agents in petrochemical sites, it is of great significance to develop an efficient and accurate targeted material.
[0003] The main technologies for remediation of DNAPL pollution, which is mainly composed of chlorine-containing pollutants, include in-situ chemical redox, permeable reaction walls, in-situ extraction treatment and microbial degradation, which are used in domestic and foreign projects. In-situ chemical redox technology injects the repair agent into the DNAPL-contaminated stratum under pressure, and purifies and removes DNAPL and oil pollutants in the water through the redox reaction between the agent and the pollutant. For example, patent application CN106269823A discloses a method for remediating soil contaminated with high concentrations of organic matter. The core of this technology is the injected oxidant or reductant. The DNAPL pollution in the soil and groundwater accumulates at the bottom of the aquifer, and the migration path is unclear under the influence of groundwater flow rate and soil heterogeneity. The agent is consumed by organic matter in the soil before acting on the DNAPL pollution, which greatly reduces its utilization rate. In-situ extraction treatment technology usually uses a power pump device to generate negative pressure to extract DNAPL and contaminated groundwater to the ground for purification treatment. For example, patent application CN212954525U discloses a system for extracting and treating heavy non-aqueous phase liquid pollutants in groundwater, and patent application CN111137941A discloses a technology for remediation of non-aqueous phase pollution in groundwater. Such extraction treatment technology lacks the pertinence of remediation and treatment, and is prone to tailing rebound of DNAPL pollution after remediation. The pollutants after extraction still need to be purified, and the overall operating cost is high. Microbial degradation technology mainly utilizes the metabolic activities of indigenous microorganisms or exogenous microorganisms to transform or degrade DNAPL pollutants into non-polluting substances. Exogenous microorganisms such as patent application CN111235077B disclose a composite biological preparation for remediating polychlorinated biphenyl contaminated soil, and patent application CN107586747B discloses a composite biological preparation and its application in remediating polychlorinated biphenyl contaminated soil, etc., but the activity of injected bacteria in such technology in complex geological environments faces huge challenges.
[0004] Among the above-mentioned technologies, in-situ reductive dechlorination is an efficient DNAPL repair technology. The main agent is zero-valent iron, which is combined with anaerobic microbial degradation to achieve the removal of chlorine-containing pollutants. In recent years, it has been highly studied. The reactions produced during reductive dechlorination are as follows:
[0005] 2Fe 0 +4H + +O 2 →2Fe 2+ +2H 2 O
[0006] Fe 0 +2H 2 O→Fe 2+ +H 2 ↑+2OH -
[0007] R-Cl+Fe 0 +H + →R-H+Fe 2+ +Cl -
[0008] 2Fe 2+ +R-Cl+H + →2Fe 3+ +R-H+Cl - .
[0009] In the process of zero-valent iron dechlorination, it also has the effect of microbial degradation, Fe 0 and the H produced by its reaction with water 2 It can serve as an electron donor for microbial metabolism to achieve biological dechlorination. Zero-valent iron can also stimulate microorganisms to secrete extracellular substances with the ability to degrade pollutants. For example, patent application CN109019819A discloses a reducing agent for in-situ remediation of groundwater contaminated by chlorinated hydrocarbons and its preparation and use methods, patent application CN114479872A discloses a moldable in-situ remediation of chlorinated hydrocarbon pollutants and its preparation method, and patent application CN114477474A discloses an in-situ remediation agent, preparation method and application for chlorinated hydrocarbon contamination of groundwater. These patents are all based on the above principles. Although the materials involved can achieve zero-valent iron-microorganism synergistic remediation of chlorinated pollutants, there are still many problems. For example, the specific selectivity of the agent materials is poor, and they will be consumed by groundwater and geochemical components after being injected into the ground, resulting in low utilization rate; during production, storage, transportation and use, the zero-valent iron component is easily oxidized; zero-valent iron will undergo various reactions with groundwater and geochemical components in a complex system, and the biological carbon source co-metabolism matrix incorporated into the above materials is easy to produce acid, resulting in passivation, flocculation and adhesion of the zero-valent iron surface, resulting in reduced electron transfer efficiency, etc.
[0010] On the premise that the concentration and distribution of low-concentration chlorinated hydrocarbon pollutants in soil and groundwater are clear, the existing groundwater in situ chemical oxidation-reduction, in situ extraction treatment and microbial degradation remediation technologies and materials can basically meet the needs of remediation and treatment. However, for chlorinated hydrocarbon pollutants existing in the DNAPL phase, there are still many problems in the accuracy and removal capacity of remediation and treatment, and there is a lack of key materials for specific selection in the face of the concealment and easy migration of chlorinated hydrocarbon DNAPL phase pollutants. Summary of the invention
[0011] The purpose of the present invention is to overcome the problems of tailing rebound and low effective utilization rate of agents in the remediation and treatment of DNAPL pollutants in the prior art and agents, the existence of multiple migration modes of DNAPL in complex strata, the irregular pollution profile making its tailing rebound phenomenon hidden and difficult to be discovered and treated in the first time, and the lack of efficient identification selectivity, and to provide a self-identifying remediation material for heavy non-aqueous phase pollutants, a preparation method and application thereof.
[0012] In order to achieve the above-mentioned object, the present invention provides a self-identifying and repairing material for heavy non-aqueous phase pollutants, wherein the self-identifying and repairing material for heavy non-aqueous phase pollutants has a multiple core-shell structure, wherein the multiple core-shell structure has a core, an intermediate layer and a coating layer which are sequentially distributed from the inside to the outside;
[0013] wherein the core contains modified zero-valent iron, an electron shuttle and a biostimulating material;
[0014] The middle layer contains a deoxidizer;
[0015] The coating layer contains a fat-soluble material.
[0016] Preferably, the particle size of the inner core is 20-35 μm.
[0017] Preferably, the core further contains a first binder;
[0018] Preferably, the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first adhesive is 100 weight %, the content of the modified zero-valent iron is 40-60 weight %, the content of the electron shuttle is 10-20 weight %, the content of the biostimulatory material is 10-40 weight %, and the content of the first adhesive is 5-15 weight %;
[0019] Preferably, the modified zero-valent iron is selected from one or more of polyethylene glycol-modified zero-valent iron, carboxymethyl cellulose-modified zero-valent iron and sodium oleate-modified zero-valent iron;
[0020] Preferably, the electron shuttle is selected from sodium anthraquinone-2,6-disulfonate and / or riboflavin;
[0021] Preferably, the biostimulant material is selected from one or more of yeast extract, nitrogen source and phosphorus source.
[0022] Preferably, the thickness of the intermediate layer is 5-10 μm.
[0023] Preferably, the intermediate layer further contains a second adhesive;
[0024] Preferably, the deoxidizer is selected from sodium sulfite, ascorbic acid, glucose oxidase and the like.
[0025] Preferably, the coating layer has a thickness of 10-20 μm.
[0026] Preferably, the fat-soluble material is selected from fatty acids and / or paraffin;
[0027] Preferably, the fatty acid is selected from C16-C20 fatty acids.
[0028] A second aspect of the present invention provides a method for preparing a self-identifying repair material, the method comprising the following steps:
[0029] S1: mixing the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder, and then granulating to obtain a core;
[0030] S2; mixing the deoxidizer, the second adhesive and the core and granulating them to form an intermediate layer on the surface of the core;
[0031] S3: heating the fat-soluble material to obtain a coating solution, and using the coating solution to coat the material obtained in step S2 to form a coating layer on the surface of the intermediate layer.
[0032] Preferably, in step S1, the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first adhesive is 100 weight %, the content of the modified zero-valent iron is 40-60 weight %, the content of the electron shuttle is 10-20 weight %, the content of the biostimulatory material is 10-40 weight %, and the content of the adhesive is 5-15 weight %;
[0033] Preferably, the modified zero-valent iron is selected from one or more of polyethylene glycol-modified zero-valent iron, carboxymethyl cellulose-modified zero-valent iron and sodium oleate-modified zero-valent iron;
[0034] Preferably, the electron shuttle is selected from sodium anthraquinone-2,6-disulfonate and / or riboflavin;
[0035] Preferably, the biostimulant material is selected from one or more of yeast extract, nitrogen source and phosphorus source.
[0036] Preferably, the particle size of the inner core is 20-35 μm.
[0037] Preferably, in step S2, the deoxidizing agent is selected from one or more of sodium sulfite, ascorbic acid and glucose oxidase.
[0038] Preferably, the ratio of the deoxidizer to the second adhesive is 5-8:1.
[0039] Preferably, in step S2, the ratio of the total weight of the deoxidizer and the second adhesive to the weight of the inner core is 1:2-3.
[0040] Preferably, in step S2, the thickness of the intermediate layer is 5-10 μm.
[0041] Preferably, the specific process of step S3 includes:
[0042] The fat-soluble material is heated to obtain a coating liquid, the material obtained in step S2 is placed in a preheated fluidized bed coater, and then the coating liquid is sprayed into the coating machine for coating, followed by drying.
[0043] Preferably, in step S3, the volume ratio of the coating liquid to the material obtained in step S2 is 1:2-5.
[0044] Preferably, in step S3, the thickness of the coating layer is 10-20 μm.
[0045] Preferably, in step S3, the fat-soluble material is selected from fatty acids and / or paraffin;
[0046] Preferably, the fatty acid is selected from C16-C20 fatty acids.
[0047] The third aspect of the present invention provides a self-identifying and repairing material for heavy non-aqueous phase pollutants prepared by the method described above.
[0048] The fourth aspect of the present invention provides the use of the self-identifying and repairing material for heavy non-aqueous phase pollutants described above in the repair of heavy non-aqueous phase pollutants.
[0049] Compared with the prior art, the present invention has the following advantages:
[0050] 1. The self-identifying and repairing material for heavy non-aqueous phase pollutants of the present invention has the function of selectively identifying DNAPL phase pollutants. When the coating layer encounters DNAPL phase pollutants or high-concentration oil in water, it can self-dissolve, thereby starting the release of DNAPL phase pollutant repair agents, and realizing timely and efficient purification and removal of DNAPL phase; it can also avoid the consumption of repair agents by geochemical and organic matter environments in soil and groundwater environments, improve the effective utilization rate of repair agents, and realize timely removal when DNAPL diffuses or rebounds and precipitates; and the coating layer can also protect the internal agent materials from oxidation.
[0051] 2. The middle layer of the self-identifying repair material for heavy non-aqueous pollutants described in the present invention contains sulfite, which can produce a deoxygenation reaction on the dissolved oxygen in the groundwater, forming an anaerobic environment that is conducive to the reduction, dechlorination and biodegradation of chlorinated hydrocarbons; it can also protect zero-valent iron and prevent it from being oxidized by water and air during storage, transportation and injection.
[0052] 3. The heavy non-aqueous phase pollutant self-identification repair material of the present invention uses modified nano zero-valent iron as the final electron donor for reduction dechlorination and anaerobic microbial degradation, and no longer adds an organic carbon source as an electron donor, thereby avoiding the degradation and acidification of the organic carbon source and causing loss of zero-valent iron. In addition, the modified nano zero-valent iron used is lipophilic, which enhances the directional removal ability of DNAPL phase and oil pollutants in water.
[0053] 4. The use of electron shuttles in combination with modified zero-valent iron in the self-identifying and repairing material for heavy non-aqueous phase pollutants described in the present invention can enhance the efficiency of electron transfer, effectively promote the reductive dechlorination ability of modified zero-valent iron, enhance the microbial degradation of chlorine-containing pollutants and secondary organic pollutants under anaerobic conditions, and reduce the passivation of the iron surface and the barrier effect of attachments. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 It is a schematic structural diagram of the self-identifying and repairing material for heavy non-aqueous phase pollutants described in the present invention.
[0055] Description of Reference Numerals
[0056] 1 coating layer 2 middle layer
[0057] 3 cores DETAILED DESCRIPTION
[0058] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0059] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0060] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating relative importance or implicitly indicating the number of technical features indicated. Therefore, unless otherwise specified, features defined as "first" and "second" may explicitly or implicitly include one or more of the features; "plurality" means two or more. The term "including" and any variation thereof means non-exclusive inclusion, and one or more other features, integers, steps, operations, units, components and / or combinations thereof may exist or be added.
[0061] The first aspect of the present invention provides a self-identifying and repairing material for heavy non-aqueous phase pollutants, Figure 1 The heavy non-aqueous phase pollutant self-identification repair material has a multiple core-shell structure, and the multiple core-shell structure has a core 3, an intermediate layer 2 and a coating layer 1 distributed in sequence from the inside to the outside;
[0062] Wherein, the core 3 contains modified zero-valent iron, electron shuttle and biostimulation material;
[0063] The intermediate layer 2 contains a deoxidizer;
[0064] The coating layer 1 contains a fat-soluble material.
[0065] In a preferred embodiment, the core 3 is in the shape of a spherical particle.
[0066] More preferably, the particle size of the core 3 is 20-35 μm.
[0067] In a preferred embodiment, the core 3 further contains a first adhesive. The use of the first adhesive is beneficial to maintaining the stability of the shape and structure of the core 3.
[0068] In a preferred embodiment, the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first adhesive is 100 weight %, the content of the modified zero-valent iron is 40-60 weight %, the content of the electron shuttle is 10-20 weight %, the content of the biostimulatory material is 10-40 weight %, and the content of the first adhesive is 5-15 weight %.
[0069] Preferably, the modified zero-valent iron is selected from one or more of polyethylene glycol-modified zero-valent iron, carboxymethyl cellulose-modified zero-valent iron and sodium oleate-modified zero-valent iron.
[0070] Preferably, the electron shuttle is selected from sodium anthraquinone-2,6-disulfonate and / or riboflavin;
[0071] Preferably, the biostimulant material is selected from one or more of yeast extract, nitrogen source and phosphorus source.
[0072] Further preferably, the nitrogen source is selected from ammonium chloride and / or potassium nitrate; and the phosphorus source is selected from disodium hydrogen phosphate and / or potassium dihydrogen phosphate.
[0073] In a preferred embodiment, when the biostimulant material is yeast extract, nitrogen source and phosphorus source, the weight ratio of the three is 10-16:8-13:1-3.
[0074] In the present invention, the use of modified zero-valent iron can reduce the agglomeration effect caused by magnetic attraction and electrostatic attraction, and its suspension fluidity and affinity with DNAPL are better; the use of electron shuttles in combination with modified zero-valent iron can promote the electron transfer efficiency of reductive dechlorination and anaerobic microbial degradation; the use of biostimulating materials can be used as inorganic nutrients in combination with zero-valent iron to stimulate the growth of indigenous microorganisms; based on this, the present invention uses a combination of modified zero-valent iron, electron shuttles and biostimulating materials as the main remediation agent, and achieves efficient removal of DNAPL phase pollutants through the reductive dechlorination-microbial anaerobic degradation process.
[0075] In a preferred embodiment, the thickness of the intermediate layer 2 is 5-10 μm.
[0076] In a preferred embodiment, the intermediate layer 2 further contains a second adhesive. The use of the second adhesive is beneficial to forming a structurally stable intermediate layer.
[0077] In a preferred embodiment, the deoxidizer is selected from one or more of sodium sulfite, ascorbic acid and glucose oxidase.
[0078] In a preferred embodiment, the thickness of the coating layer 1 is 10-20 μm, and more preferably
[0079] In a preferred embodiment, the fat-soluble material is selected from fatty acids and / or paraffin.
[0080] More preferably, the fatty acid is selected from C16-C20 fatty acids. For example, stearic acid,
[0081] In the present invention, the main component of the coating layer is a fat-soluble material, so that when the self-identification repair material contacts the DNAPL phase or the oil pollutant in the high-concentration water, the coating layer can be dissolved, thereby self-identification starts to release the DNAPL phase pollutant repair agent in the shell, and the dissolution time is about 2-5 minutes. The intermediate layer contains a deoxidizer. When the coating layer recognizes that the DNAPL phase is dissolved, the deoxidizer can be released. The deoxidizer reacts with the dissolved oxygen in the groundwater to produce an anaerobic environment. The dissolved oxygen in the groundwater is less than 0.1 mg / L, and the anaerobic environment can last for 50 to 70 days. After the intermediate layer releases the deoxidizer, the modified zero-valent iron, electron shuttle and biostimulant contained in the kernel are released into the anaerobic environment created by the deoxidizer. Through the mutual cooperation of the modified zero-valent iron, electron shuttle and biostimulant, the purification and removal of the DNAPL phase and the oil pollutants in the water can be achieved based on the synergistic effect of reductive dechlorination-microbial anaerobic degradation.
[0082] A second aspect of the present invention provides a method for preparing a self-identifying repair material for heavy non-aqueous phase pollutants, the method comprising the following steps:
[0083] S1: mixing the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder, and then granulating to obtain a core;
[0084] S2; mixing the deoxidizer, the second adhesive and the core and granulating them to form an intermediate layer on the surface of the core;
[0085] S3: heating the fat-soluble material to obtain a coating solution, and using the coating solution to coat the material obtained in step S2 to form a coating layer on the surface of the intermediate layer.
[0086] In a preferred embodiment, the specific process of step S1 includes: in the presence of a protective gas, the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first adhesive are mixed in a mixing granulator, and then ethanol is added to continue mixing, and then the temperature is raised to 50° C. by a uniform program heating method to gradually complete granulation.
[0087] In the present invention, in step S1, ethanol is added during the granulation process to facilitate the full mixing of the raw materials.
[0088] Further preferably, in step S1, the amount of ethanol used is 30-50 weight % of the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first adhesive.
[0089] In a preferred embodiment, in step S1, the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first adhesive is 100%, the content of the modified zero-valent iron is 40-60% by weight, the content of the electron shuttle is 10-20% by weight, the content of the biostimulatory material is 10-40% by weight, and the content of the adhesive is 5-15% by weight.
[0090] Further preferably, in step S1, the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first adhesive is 100%, the content of the modified zero-valent iron is 45-55% by weight, the content of the electron shuttle is 12-16% by weight, the content of the biostimulatory material is 20-35% by weight, and the content of the first adhesive is 7-12% by weight.
[0091] Further preferably, the modified zero-valent iron is selected from one or more of polyethylene glycol-modified zero-valent iron, carboxymethyl cellulose-modified zero-valent iron and sodium oleate-modified zero-valent iron.
[0092] Further preferably, the electron shuttle is selected from sodium anthraquinone-2,6-disulfonate and / or riboflavin.
[0093] Further preferably, the biostimulant material is selected from one or more of yeast extract, nitrogen source and phosphorus source.
[0094] Further preferably, the nitrogen source is selected from ammonium chloride and / or potassium nitrate; and the phosphorus source is selected from disodium hydrogen phosphate and / or potassium dihydrogen phosphate.
[0095] In a preferred embodiment, when the biostimulant material is yeast extract, nitrogen source and phosphorus source, the weight ratio of the three is 10-16:8-13:1-3.
[0096] Further preferably, the first adhesive may be an adhesive commonly used in the art. In a specific embodiment, the first adhesive is polyvinyl pyrrolidone.
[0097] In a preferred embodiment, in step S1, the shape of the inner core is spherical.
[0098] In a preferred embodiment, the particle size of the core is 20-35 μm; specifically, it can be 20 μm, 25 μm, 30 μm or 35 μm.
[0099] In a preferred embodiment, the specific process of step S2 includes: mixing the deoxidizer, the second adhesive and ethanol to obtain a mixture, adding the mixture to the mixing granulator used in step S1, mixing with the core obtained in step S1, and then granulating to form an intermediate layer on the surface of the core.
[0100] In a preferred embodiment, in step S2, the deoxidizing agent is selected from one or more of sodium sulfite, ascorbic acid and glucose oxidase.
[0101] More preferably, the weight ratio of the deoxidizer to the second adhesive is 5-8:1.
[0102] Further preferably, the second adhesive may be an adhesive commonly used in the art. In a specific embodiment, the second adhesive is polyvinyl pyrrolidone.
[0103] In a preferred embodiment, in step S2, the ratio of the total weight of the deoxidizer and the second adhesive to the weight of the inner core is 1:2-3.
[0104] In a preferred embodiment, in step S2, the amount of ethanol used is 20-40 weight % of the total weight of the deoxidizer and the second adhesive.
[0105] In a preferred embodiment, in step S2, the thickness of the intermediate layer is 5-10 μm.
[0106] In the method of the present invention, there is no special requirement for the granulation in steps S1 and S2, and the granulation can be carried out by conventional granulation methods in the art.
[0107] In a preferred embodiment, the specific process of step S3 includes:
[0108] The fat-soluble material is heated to obtain a coating liquid, the material obtained in step S2 is placed in a preheated fluidized bed coater, and then the coating liquid is sprayed into the coating machine for coating, followed by drying.
[0109] In a preferred embodiment, in step S3, the volume ratio of the coating liquid to the material obtained in step S2 is 1:2-5.
[0110] In a preferred embodiment, in step S3, the thickness of the coating layer is 10-20 μm.
[0111] In a preferred embodiment, in step S3, the fat-soluble material is selected from fatty acids and / or paraffin.
[0112] Further preferably, the fatty acid is selected from C16-C20 fatty acids.
[0113] In a preferred embodiment, the preheating temperature is 70-80°C.
[0114] In a preferred embodiment, the heating temperature is 80-90°C.
[0115] In a preferred embodiment, the drying temperature is 30-40° C. and the drying time is 1-2 h.
[0116] The third aspect of the present invention provides a self-identifying and repairing material for heavy non-aqueous phase pollutants prepared by the method described above.
[0117] The fourth aspect of the present invention provides the use of the self-identifying and repairing material for heavy non-aqueous phase pollutants described above in the repair of heavy non-aqueous phase pollutants.
[0118] The self-identifying repair material described in the present invention can be injected into the target contaminated area or diffusion area of chlorinated hydrocarbon DNAPL phase pollutants by means of in-situ high-pressure injection; it can also be used as a filling material to be filled into the bottom of the permeable reaction wall of the chlorinated hydrocarbon contaminated site; it can also be used as a supporting material for in-situ extraction treatment and injected into the DNAPL phase rebound area in the later stage of the extraction treatment.
[0119] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.
[0120] Unless otherwise specified, other reagents used in the following examples and comparative examples are commercially available products.
[0121] Example 1
[0122] S1: In the presence of protective gas (nitrogen), modified zero-valent iron (polyethylene glycol modified zero-valent iron), electron shuttle (sodium anthraquinone-2,6-disulfonate), biostimulatory material (yeast extract, ammonium chloride and potassium dihydrogen phosphate) and a first binder (polyvinyl pyrrolidone) are mixed in a mixing granulator, and then ethanol is added to continue mixing, followed by granulation at 50°C and 150rpm to obtain a core with a diameter of 25 μm; wherein the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder is 100 weight%, the content of the modified zero-valent iron is 47 weight%, the content of the electron shuttle is 15 weight%, the content of the biostimulatory material is 26 weight%, and the content of the binder is 12 weight%; the weight ratio of yeast extract, nitrogen source (ammonium chloride) and phosphorus source (potassium dihydrogen phosphate) is 13:10:3; the amount of ethanol is 40 weight% of the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder;
[0123] S2: Mix a deoxidizer (sodium sulfite), a second adhesive (polyvinyl pyrrolidone) and ethanol to obtain a mixture, add the mixture to the mixing granulator used in step S1, mix with the inner core obtained in step S1, and then granulate, the mixing granulation speed is 500 rpm, the granulation temperature is 50° C., and an intermediate layer is formed on the surface of the inner core, and the thickness of the intermediate layer is 6 μm; wherein the weight ratio of the deoxidizer to the second adhesive is 6:1; the ratio of the total weight of the deoxidizer and the second adhesive to the weight of the inner core obtained in step S1 is 1:3; the amount of ethanol is 30% by weight of the total weight of the deoxidizer and the second adhesive;
[0124] S3: Heat the fat-soluble material (paraffin) to 90°C to obtain a coating solution, place the material obtained in step S2 in a fluidized bed coater preheated to 75°C, and then spray the coating solution for coating, followed by drying at 35°C for 2h to form a coating layer on the surface of the intermediate layer, the thickness of the coating layer is 12 μm; wherein the volume ratio of the coating solution to the material obtained in step S2 is 1:4.
[0125] Example 2
[0126] S1: In the presence of protective gas (nitrogen), modified zero-valent iron (polyethylene glycol modified zero-valent iron), electron shuttle (sodium anthraquinone-2,6-disulfonate), biostimulatory material (yeast extract, ammonium chloride and potassium dihydrogen phosphate) and a first binder (polyvinyl pyrrolidone) are mixed in a mixing granulator, and then ethanol is added to continue mixing, followed by granulation at 150 rpm and 50° C. to obtain a core with a diameter of 25 μm; wherein the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder is 100 weight%, the content of the modified zero-valent iron is 47 weight%, the content of the electron shuttle is 15 weight%, the content of the biostimulatory material is 26 weight%, and the content of the binder is 12 weight%; the weight ratio of yeast extract, nitrogen source (ammonium chloride) and phosphorus source (potassium dihydrogen phosphate) is 13:10:3; the amount of ethanol is 40 weight% of the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder;
[0127] S2: Mix a deoxidizer (sodium sulfite), a second adhesive (polyvinyl pyrrolidone) and ethanol to obtain a mixture, add the mixture to the mixing granulator used in step S1, mix with the inner core obtained in step S1, and then granulate, mix and granulate at 600rpm, the granulation temperature is 50°C, and an intermediate layer is formed on the surface of the inner core, and the thickness of the intermediate layer is 6μm; wherein the weight ratio of the deoxidizer to the second adhesive is 7:1; the ratio of the total weight of the deoxidizer and the second adhesive to the weight of the inner core obtained in step S1 is 1:3; the amount of ethanol is 30 weight% of the total weight of the deoxidizer and the second adhesive;
[0128] S3: Heat the fat-soluble material (paraffin) to 90°C to obtain a coating solution, place the material obtained in step S2 in a fluidized bed coater preheated to 75°C, and then spray the coating solution for coating, followed by drying at 35°C for 2h to form a coating layer on the surface of the intermediate layer, the thickness of the coating layer is 10 μm; wherein the volume ratio of the coating solution to the material obtained in step S2 is 1:5.
[0129] Example 3
[0130] S1: In the presence of protective gas (nitrogen), modified zero-valent iron (polyethylene glycol modified zero-valent iron), electron shuttle (sodium anthraquinone-2,6-disulfonate), biostimulatory material (yeast extract, ammonium chloride and potassium dihydrogen phosphate) and a first binder (polyvinyl pyrrolidone) are mixed in a mixing granulator, and then ethanol is added to continue mixing, followed by granulation at 200 rpm and 50° C. to obtain a core with a diameter of 25 μm; wherein the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder is 100 weight%, the content of the modified zero-valent iron is 47 weight%, the content of the electron shuttle is 15 weight%, the content of the biostimulatory material is 26 weight%, and the content of the binder is 12 weight%; the weight ratio of yeast extract, nitrogen source (ammonium chloride) and phosphorus source (potassium dihydrogen phosphate) is 13:10:3; the amount of ethanol is 40 weight% of the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder;
[0131] S2: Mix a deoxidizer (ascorbic acid), a second adhesive (polyvinyl pyrrolidone) and ethanol to obtain a mixture, add the mixture into the mixing granulator used in step S1, mix with the inner core obtained in step S1, and then granulate, mix and granulate at 600rpm, the granulation temperature is 50°C, and an intermediate layer is formed on the surface of the inner core, and the thickness of the intermediate layer is 5μm; wherein the weight ratio of the deoxidizer to the second adhesive is 6:1; the ratio of the total weight of the deoxidizer and the second adhesive to the weight of the inner core obtained in step S1 is 1:3; the amount of ethanol is 30 weight% of the total weight of the deoxidizer and the second adhesive;
[0132] S3: Heat the fat-soluble material (paraffin and stearic acid in a weight ratio of 1:1) to 90°C to obtain a coating solution, place the material obtained in step S2 in a fluidized bed coater preheated to 75°C, and then spray the coating solution for coating, followed by drying at 35°C for 2h to form a coating layer on the surface of the intermediate layer, and the thickness of the coating layer is 13 μm; wherein the volume ratio of the coating solution to the material obtained in step S2 is 1:4.
[0133] Example 4
[0134] S1: In the presence of protective gas (nitrogen), modified zero-valent iron (polyethylene glycol modified zero-valent iron), electron shuttle (riboflavin), biostimulatory material (yeast extract, ammonium chloride and potassium dihydrogen phosphate) and a first binder (polyvinyl pyrrolidone) are mixed in a mixing granulator, and then ethanol is added to continue mixing, followed by granulation at 150 rpm and 50° C. to obtain a core with a diameter of 25 μm; wherein the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder is 100 weight%, the content of the modified zero-valent iron is 47 weight%, the content of the electron shuttle is 15 weight%, the content of the biostimulatory material is 26 weight%, and the content of the binder is 12 weight%; the weight ratio of yeast extract, nitrogen source (ammonium chloride) and phosphorus source (potassium dihydrogen phosphate) is 13:10:3; the amount of ethanol is 40 weight% of the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder;
[0135] S2: Mix a deoxidizer (sodium sulfite), a second adhesive (polyvinyl pyrrolidone) and ethanol to obtain a mixture, add the mixture into the mixing granulator used in step S1, mix with the inner core obtained in step S1, and then granulate, the mixing granulation speed is 600 rpm, the granulation temperature is 50° C., and an intermediate layer is formed on the surface of the inner core, and the thickness of the intermediate layer is 6 μm; wherein the weight ratio of the deoxidizer to the second adhesive is 7:1; the ratio of the total weight of the deoxidizer and the second adhesive to the weight of the inner core obtained in step S1 is 1:3; the amount of ethanol is 30% by weight of the total weight of the deoxidizer and the second adhesive;
[0136] S3: Heat the fat-soluble material (stearic acid) to 90°C to obtain a coating solution, place the material obtained in step S2 in a fluidized bed coater preheated to 75°C, and then spray the coating solution for coating, followed by drying at 35°C for 2h to form a coating layer on the surface of the intermediate layer, the thickness of the coating layer is 11 μm; wherein the volume ratio of the coating solution to the material obtained in step S2 is 1:5.
[0137] Example 5
[0138] S1: In the presence of protective gas (nitrogen), modified zero-valent iron (carboxymethyl cellulose modified zero-valent iron), electron shuttle (sodium anthraquinone-2,6-disulfonate), biostimulant material (yeast extract, potassium nitrate and disodium hydrogen phosphate) and a first binder (polyvinyl pyrrolidone) are mixed in a mixing granulator, and then ethanol is added to continue mixing, followed by granulation at 150 rpm and 50° C. to obtain a core with a diameter of 23 μm; wherein the total weight of the modified zero-valent iron, the electron shuttle, the biostimulant material and the first binder is 100 weight%, the content of the modified zero-valent iron is 50 weight%, the content of the electron shuttle is 12 weight%, the content of the biostimulant material is 29 weight%, and the content of the binder is 9 weight%; the weight ratio of yeast extract, nitrogen source (potassium nitrate) and phosphorus source (disodium hydrogen phosphate) is 15:12:2; the amount of ethanol is 40 weight% of the total weight of the modified zero-valent iron, the electron shuttle, the biostimulant material and the first binder;
[0139] S2: Mix a deoxidizer (sodium sulfite), a second adhesive (polyvinyl pyrrolidone) and ethanol to obtain a mixture, add the mixture into the mixing granulator used in step S1, mix with the inner core obtained in step S1, and then granulate, the mixing granulation speed is 600 rpm, the granulation temperature is 50° C., and an intermediate layer is formed on the surface of the inner core, and the thickness of the intermediate layer is 8 μm; wherein the weight ratio of the deoxidizer to the second adhesive is 6:1; the ratio of the total weight of the deoxidizer and the second adhesive to the weight of the inner core obtained in step S1 is 1:3; the amount of ethanol is 30% by weight of the total weight of the deoxidizer and the second adhesive;
[0140] S3: Heat the fat-soluble material (paraffin) to 90°C to obtain a coating solution, place the material obtained in step S2 in a fluidized bed coater preheated to 75°C, and then spray the coating solution for coating, followed by drying at 35°C for 2h to form a coating layer on the surface of the intermediate layer, the thickness of the coating layer is 12 μm; wherein the volume ratio of the coating solution to the material obtained in step S2 is 1:4.
[0141] Example 6
[0142] S1: In the presence of protective gas (nitrogen), modified zero-valent iron (carboxymethyl cellulose modified zero-valent iron), electron shuttle (riboflavin), biostimulatory material (yeast extract, potassium nitrate and disodium hydrogen phosphate) and a first binder (polyvinyl pyrrolidone) are mixed in a mixing granulator, and then ethanol is added to continue mixing, followed by granulation at 200 rpm and 50° C. to obtain a core with a diameter of 25 μm; wherein the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder is 100 weight%, the content of the modified zero-valent iron is 50 weight%, the content of the electron shuttle is 12 weight%, the content of the biostimulatory material is 29 weight%, and the content of the binder is 9 weight%; the weight ratio of yeast extract, nitrogen source (potassium nitrate) and phosphorus source (disodium hydrogen phosphate) is 15:12:2; the amount of ethanol is 40 weight% of the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder;
[0143] S2: Mix a deoxidizer (sodium sulfite), a second adhesive (polyvinyl pyrrolidone) and ethanol to obtain a mixture, add the mixture into the mixing granulator used in step S1, mix with the inner core obtained in step S1, and then granulate, the mixing granulation speed is 600 rpm, the granulation temperature is 50° C., and an intermediate layer is formed on the surface of the inner core, and the thickness of the intermediate layer is 8 μm; wherein the weight ratio of the deoxidizer to the second adhesive is 6:1; the ratio of the total weight of the deoxidizer and the second adhesive to the weight of the inner core obtained in step S1 is 1:3; the amount of ethanol is 30% by weight of the total weight of the deoxidizer and the second adhesive;
[0144] S3: Heat the fat-soluble material (paraffin) to 90°C to obtain a coating solution, place the material obtained in step S2 in a fluidized bed coater preheated to 75°C, and then spray the coating solution for coating, followed by drying at 35°C for 2h to form a coating layer on the surface of the intermediate layer, the thickness of the coating layer is 12 μm; wherein the volume ratio of the coating solution to the material obtained in step S2 is 1:4.
[0145] Example 7
[0146] S1: In the presence of protective gas (nitrogen), modified zero-valent iron (carboxymethyl cellulose modified zero-valent iron), electron shuttle (sodium anthraquinone-2,6-disulfonate), biostimulatory material (yeast extract, potassium nitrate and disodium hydrogen phosphate) and a first binder (polyvinyl pyrrolidone) are mixed in a mixing granulator, and then ethanol is added to continue mixing, followed by granulation at 200 rpm and 50° C. to obtain a core with a diameter of 23 μm; wherein the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder is 100 weight%, the content of the modified zero-valent iron is 50 weight%, the content of the electron shuttle is 12 weight%, the content of the biostimulatory material is 29 weight%, and the content of the binder is 9 weight%; the weight ratio of yeast extract, nitrogen source (potassium nitrate) and phosphorus source (disodium hydrogen phosphate) is 15:12:2; the amount of ethanol is 40 weight% of the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder;
[0147] S2: Mix a deoxidizer (sodium sulfite), a second adhesive (polyvinyl pyrrolidone) and ethanol to obtain a mixture, add the mixture into the mixing granulator used in step S1, mix with the inner core obtained in step S1, and then granulate, the mixing granulation speed is 600 rpm, the granulation temperature is 50° C., and an intermediate layer is formed on the surface of the inner core, and the thickness of the intermediate layer is 8 μm; wherein the weight ratio of the deoxidizer to the second adhesive is 6:1; the ratio of the total weight of the deoxidizer and the second adhesive to the weight of the inner core obtained in step S1 is 1:3; the amount of ethanol is 30% by weight of the total weight of the deoxidizer and the second adhesive;
[0148] S3: Heat the fat-soluble material (paraffin and stearic acid in a weight ratio of 1:1) to 90°C to obtain a coating solution, place the material obtained in step S2 in a fluidized bed coater preheated to 75°C, and then spray the coating solution for coating, followed by drying at 35°C for 2h to form a coating layer on the surface of the intermediate layer, and the thickness of the coating layer is 13 μm; wherein the volume ratio of the coating solution to the material obtained in step S2 is 1:4.
[0149] Example 8
[0150] S1: In the presence of protective gas (nitrogen), modified zero-valent iron (sodium oleate modified zero-valent iron), electron shuttle (sodium anthraquinone-2,6-disulfonate), biostimulatory material (yeast extract, potassium nitrate and disodium hydrogen phosphate) and a first binder (polyvinyl pyrrolidone) are mixed in a mixing granulator, and then ethanol is added to continue mixing, followed by granulation at 150 rpm and 50° C. to obtain a core with a diameter of 28 μm; wherein the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder is 100 weight%, the content of the modified zero-valent iron is 48 weight%, the content of the electron shuttle is 14 weight%, the content of the biostimulatory material is 26 weight%, and the content of the binder is 12 weight%; the weight ratio of yeast extract, nitrogen source (potassium nitrate) and phosphorus source (disodium hydrogen phosphate) is 12:12:2; the amount of ethanol is 40 weight% of the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder;
[0151] S2: Mix a deoxidizer (sodium sulfite), a second adhesive (polyvinyl pyrrolidone) and ethanol to obtain a mixture, add the mixture to the mixing granulator used in step S1, mix with the inner core obtained in step S1, and then granulate, the mixing granulation speed is 600 rpm, the granulation temperature is 50° C., and an intermediate layer is formed on the surface of the inner core, and the thickness of the intermediate layer is 7 μm; wherein the weight ratio of the deoxidizer to the second adhesive is 7:1; the ratio of the total weight of the deoxidizer and the second adhesive to the weight of the inner core obtained in step S1 is 1:3; the amount of ethanol is 30% by weight of the total weight of the deoxidizer and the second adhesive;
[0152] S3: Heat the fat-soluble material (paraffin) to 90°C to obtain a coating solution, place the material obtained in step S2 in a fluidized bed coater preheated to 75°C, and then spray the coating solution for coating, followed by drying at 4°C for 2h to form a coating layer on the surface of the intermediate layer, the thickness of the coating layer is 10 μm; wherein the volume ratio of the coating solution to the material obtained in step S2 is 1:4.5.
[0153] Example 9
[0154] S1: In the presence of protective gas (nitrogen), modified zero-valent iron (sodium oleate modified zero-valent iron), electron shuttle (riboflavin), biostimulatory material (yeast extract, potassium nitrate and disodium hydrogen phosphate) and a first binder (polyvinyl pyrrolidone) are mixed in a mixing granulator, and then ethanol is added to continue mixing, followed by granulation at 150 rpm and 50° C. to obtain a core with a diameter of 30 μm; wherein the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder is 100 weight%, the content of the modified zero-valent iron is 48 weight%, the content of the electron shuttle is 14 weight%, the content of the biostimulatory material is 26 weight%, and the content of the binder is 12 weight%; the weight ratio of yeast extract, nitrogen source (potassium nitrate) and phosphorus source (disodium hydrogen phosphate) is 12:12:2; the amount of ethanol is 40 weight% of the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder;
[0155] S2: Mix a deoxidizer (sodium sulfite), a second adhesive (polyvinyl pyrrolidone) and ethanol to obtain a mixture, add the mixture to the mixing granulator used in step S1, mix with the inner core obtained in step S1, and then granulate, the mixing granulation speed is 500 rpm, the granulation temperature is 50° C., and an intermediate layer is formed on the surface of the inner core, and the thickness of the intermediate layer is 7 μm; wherein the weight ratio of the deoxidizer to the second adhesive is 7:1; the ratio of the total weight of the deoxidizer and the second adhesive to the weight of the inner core obtained in step S1 is 1:3; the amount of ethanol is 30% by weight of the total weight of the deoxidizer and the second adhesive;
[0156] S3: Heat the fat-soluble material (paraffin) to 90°C to obtain a coating solution, place the material obtained in step S2 in a fluidized bed coater preheated to 75°C, and then spray the coating solution for coating, followed by drying at 40°C for 1h to form a coating layer on the surface of the intermediate layer, the thickness of the coating layer is 10 μm; wherein the volume ratio of the coating solution to the material obtained in step S2 is 1:4.5.
[0157] Example 10
[0158] S1: In the presence of protective gas (nitrogen), modified zero-valent iron (sodium oleate modified zero-valent iron), electron shuttle (riboflavin), biostimulatory material (yeast extract, potassium nitrate and disodium hydrogen phosphate) and a first binder (polyvinyl pyrrolidone) are mixed in a mixing granulator, and then ethanol is added to continue mixing, followed by granulation at 150rpm and 50°C to obtain a core with a diameter of 28μm; wherein the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder is 100wt%, the content of the modified zero-valent iron is 48wt%, the content of the electron shuttle is 14wt%, the content of the biostimulatory material is 26wt%, and the content of the binder is 12wt%; the weight ratio of yeast extract, nitrogen source (potassium nitrate) and phosphorus source (disodium hydrogen phosphate) is 12:12:2; the amount of ethanol is 40wt% of the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder;
[0159] S2: Mix a deoxidizer (sodium sulfite), a second adhesive (polyvinyl pyrrolidone) and ethanol to obtain a mixture, add the mixture to the mixing granulator used in step S1, mix with the inner core obtained in step S1, and then granulate, the mixing granulation speed is 500 rpm, the granulation temperature is 50° C., and an intermediate layer is formed on the surface of the inner core, and the thickness of the intermediate layer is 7 μm; wherein the weight ratio of the deoxidizer to the second adhesive is 7:1; the ratio of the total weight of the deoxidizer and the second adhesive to the weight of the inner core obtained in step S1 is 1:3; the amount of ethanol is 30% by weight of the total weight of the deoxidizer and the second adhesive;
[0160] S3: Heat the fat-soluble material (paraffin and stearic acid in a weight ratio of 1:1) to 90°C to obtain a coating solution, place the material obtained in step S2 in a fluidized bed coater preheated to 75°C, and then spray the coating solution for coating, followed by drying at 40°C for 1h to form a coating layer on the surface of the intermediate layer, and the thickness of the coating layer is 12 μm; wherein the volume ratio of the coating solution to the material obtained in step S2 is 1:4.5.
[0161] Comparative Example 1
[0162] The method described in Example 5 is followed, except that step S3 is not performed.
[0163] Comparative Example 2
[0164] The method described in Example 5 is followed, except that steps S2 and S3 are not performed.
[0165] Comparative Example 3
[0166] S1: In the presence of protective gas (nitrogen), modified zero-valent iron (carboxymethyl cellulose modified zero-valent iron), biostimulatory material (yeast extract, potassium nitrate and disodium hydrogen phosphate) and a first binder (polyvinyl pyrrolidone) are mixed in a mixing granulator, and then ethanol is added to continue mixing, followed by granulation at 150 rpm and 50° C. to obtain a core with a diameter of 22 μm; wherein the total weight of the modified zero-valent iron, the biostimulatory material and the first binder is 100 weight%, the content of the modified zero-valent iron is 55 weight%, the content of the biostimulatory material is 35 weight%, and the content of the binder is 10 weight%; the weight ratio of yeast extract, nitrogen source (potassium nitrate) and phosphorus source (disodium hydrogen phosphate) is 18:13:4; the amount of ethanol is 40 weight% of the total weight of the modified zero-valent iron, the biostimulatory material and the first binder;
[0167] S2: Mix a deoxidizer (sodium sulfite), a second adhesive (polyvinyl pyrrolidone) and ethanol to obtain a mixture, add the mixture into the mixing granulator used in step S1, mix with the inner core obtained in step S1, and then granulate, the mixing granulation speed is 600 rpm, the granulation temperature is 50° C., and an intermediate layer is formed on the surface of the inner core, and the thickness of the intermediate layer is 8 μm; wherein the weight ratio of the deoxidizer to the second adhesive is 6:1; the ratio of the total weight of the deoxidizer and the second adhesive to the weight of the inner core obtained in step S1 is 1:3; the amount of ethanol is 30% by weight of the total weight of the deoxidizer and the second adhesive;
[0168] S3: Heat the fat-soluble material (paraffin) to 90°C to obtain a coating solution, place the material obtained in step S2 in a fluidized bed coater preheated to 75°C, and then spray the coating solution for coating, followed by drying at 35°C for 2h to form a coating layer on the surface of the intermediate layer, the thickness of the coating layer is 12 μm; wherein the volume ratio of the coating solution to the material obtained in step S2 is 1:4.
[0169] Test Example 1
[0170] The properties of the products prepared in Examples 1-10 and Comparative Example 3 were tested, and the test results are shown in Table 1. The test method is as follows:
[0171] Add the sample to be tested into a glass beaker containing 1L of tap water and stir with a glass rod for 10 minutes every day. After leaving it for 15 days, the iron ion concentration in the water is tested. At the same time, the chloride ion concentration in the water is tested. Then, add 5mL of trichloroethylene to sink to the bottom of the beaker to form DNAPL. Continue to leave it for 3 days and then test the chloride ion content.
[0172] The performance of the product prepared in Comparative Example 1-2 was tested, and the test results are shown in Table 2. The test method is as follows:
[0173] Add the sample to be tested into a glass beaker containing 1L of tap water and stir with a glass rod for 10 minutes every day. After leaving it for 3 days, the iron ion concentration in the water is tested. At the same time, the initial chloride ion concentration in the water is tested. Then, add 5mL of trichloroethylene to sink to the bottom of the beaker to form DNAPL. Continue to leave it for 3 days and then test the chloride ion content.
[0174] Table 1
[0175] Sample input amount 15d Iron ion concentration 15d chloride concentration 18d Chloride ion concentration Example 1 10g <0.2mg / L 0.47mg / L 2415mg / L Example 2 10g <0.2mg / L 0.43mg / L 2372mg / L Example 3 10g <0.2mg / L 0.37mg / L 2504mg / L Example 4 10g <0.2mg / L 0.58mg / L 2351mg / L Example 5 10g <0.2mg / L 0.51mg / L 2460mg / L Example 6 10g <0.2mg / L 0.41mg / L 2372mg / L Example 7 10g <0.2mg / L 0.48mg / L 2575mg / L Example 8 10g <0.2mg / L 0.46mg / L 2419mg / L Example 9 10g <0.2mg / L 0.47mg / L 2085mg / L Example 10 10g <0.2mg / L 0.51mg / L 2605mg / L Comparative Example 3 10g <0.2mg / L 0.39mg / L 1508mg / L
[0176] Table 2
[0177] Sample input amount 3d Iron ion concentration 3d Chloride ion concentration 6d chloride ion concentration Comparative Example 1 9g 31mg / L 0.47mg / L 672mg / L Comparative Example 2 7g 95mg / L 0.47mg / L 71mg / L
[0178] During the performance test of the products prepared in Examples 1-10 and Comparative Example 3, after adding trichloroethylene, it can be observed that the samples to be tested are dissolved and damaged one after another, and the turbidity of the water in the beaker gradually increases, showing brown-green turbidity. Combined with the data in Table 1, it can be seen that the products prepared in the examples can achieve specific self-recognition of chlorinated hydrocarbon DNAPL phase pollutants and can efficiently remove chlorine from trichloroethylene. Although the product prepared in Comparative Example 3 can identify chlorinated hydrocarbons, its dechlorination ability is relatively low.
[0179] During the performance test of the product prepared in Comparative Example 1, the sample to be tested was added to tap water and stirred for 3 days. It was observed that part of the sample was suspended in the tap water, and the iron ion concentration in the water body increased rapidly. Combined with the data in Table 2, it can be seen that the dechlorination capacity of the product prepared in Comparative Example 1 is low, and the zero-valent iron is lost.
[0180] During the performance test of the product prepared in Comparative Example 2, the sample to be tested was added to tap water and stirred for 3 days. It can be observed that part of the sample exists in a suspended state in the tap water, and the iron ion concentration in the water increases rapidly. Combined with the data in Table 2, it can be seen that the product prepared in Comparative Example 2 can only remove a small amount of chlorine, and the loss of zero-valent iron is large.
[0181] Application Example 1
[0182] The application site is a petrochemical contaminated site. The site is mainly modern chemical industry, producing various aldehydes, epoxy compounds, butyl rubber, plasticizers and acetonitrile series. The previous site investigation showed that the pollutants detected in the groundwater include polycyclic aromatic hydrocarbons, phenols and chlorinated hydrocarbons; the total area of the site is 0.7km 2 The groundwater is buried at a depth of 1.8 to 3 meters all year round. The soil layers from top to bottom are plain fill, silt, clay, and bedrock. The first waterproof bottom plate is 6 to 9 meters deep. The groundwater permeability coefficient is 3.8×10 -6m / s. The elevation difference of this block is large, which is easy to cause pollution migration with seasonal precipitation. DNAPL phase pollutants of chlorinated hydrocarbons were detected near the waterproof bottom plate in two wells. Ground penetrating radar was used to characterize the DNAPL phase pollution range of chlorinated hydrocarbons. The pollution area in the A monitoring well area is about 37m 2 . The product prepared in Example 3 was used for direct-push differential pressure injection at 20 points in the A monitoring well area. The injection amount at each point was 10 kg and the injection depth was 8 to 8.5 m. Then the change of chloride ion concentration was continuously observed in the A monitoring well. During the 107-day monitoring, the chloride ion concentration continued to rise, and the rise was faster in the early stage, reaching 1300 mg / L on the 30th day and 2100 mg / L on the 107th day. The ground penetrating radar was used to detect the changes in the scope of DNAPL phase chlorinated hydrocarbon pollution, and the DNAPL phase occurrence area was reduced by 78%.
[0183] Application Example 2
[0184] The application site is a petrochemical contaminated site. The site is mainly engaged in oil refining and chemical industry. The products are finished oil, cyclohexane, chloropropylene, etc. The previous site investigation found complex pollutants such as LNAPL and DNAPL. The site selected the multiphase extraction and treatment remediation technology, and a total of 11428m 3 After the groundwater is pumped out, there is still about 10m of contamination at the water-proof bottom plate of the pollution source. 2 The DNAPL phase of chlorinated hydrocarbons was repeatedly tailed and precipitated in a small area. To address this problem, 5 injection points were arranged in the local area, and 20 kg of the product prepared in Example 10 was injected at a pressure of 0.8-1 MPa at the water-proof bottom plate, and continuous monitoring was performed after injection. The chloride ion content increased from the initial 27 mg / L to 1307 mg / L within 83 days, indicating that the dechlorination effect was significant. No obvious DNAPL phase chlorinated hydrocarbon pollutants were detected after the 68th day.
[0185] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A self-identifying and repairing material for heavy non-aqueous phase pollutants, characterized in that: The heavy non-aqueous phase pollutant self-identification repair material has a multiple core-shell structure, wherein the multiple core-shell structure has a core (3), an intermediate layer (2) and a coating layer (1) which are sequentially distributed from the inside to the outside; wherein the core (3) contains modified zero-valent iron, an electron shuttle and a biostimulating material; The intermediate layer (2) contains a deoxidizer; The coating layer (1) contains a fat-soluble material.
2. The heavy non-aqueous phase pollutant self-identification repair material according to claim 1, characterized in that: The particle size of the core (3) is 20-35 μm.
3. The heavy non-aqueous phase pollutant self-identification repair material according to claim 1 or 2, characterized in that: The core (3) further contains a first adhesive; Preferably, the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first adhesive is 100 weight %, the content of the modified zero-valent iron is 40-60 weight %, the content of the electron shuttle is 10-20 weight %, the content of the biostimulatory material is 10-40 weight %, and the content of the first adhesive is 5-15 weight %; Preferably, the modified zero-valent iron is selected from one or more of polyethylene glycol-modified zero-valent iron, carboxymethyl cellulose-modified zero-valent iron and sodium oleate-modified zero-valent iron; Preferably, the electron shuttle is selected from sodium anthraquinone-2,6-disulfonate and / or riboflavin; Preferably, the biostimulant material is selected from one or more of yeast extract, nitrogen source and phosphorus source.
4. The heavy non-aqueous phase pollutant self-identification repair material according to any one of claims 1 to 3, characterized in that: The thickness of the intermediate layer (2) is 5-10 μm.
5. The heavy non-aqueous phase pollutant self-identification repair material according to claim 1 or 4, characterized in that: The intermediate layer (2) further contains a second adhesive; Preferably, the deoxidizer is selected from one or more of sodium sulfite, ascorbic acid and glucose oxidase.
6. The heavy non-aqueous phase pollutant self-identification repair material according to claim 1 or 4, characterized in that: The coating layer (1) has a thickness of 10-20 μm.
7. The heavy non-aqueous phase pollutant self-identification repair material according to any one of claims 1 to 6, characterized in that: The fat-soluble material is selected from fatty acids and / or paraffin; Preferably, the fatty acid is selected from C16-C20 fatty acids.
8. A method for preparing a self-identifying and repairing material for heavy non-aqueous phase pollutants, characterized in that: The method comprises the following steps: S1: mixing the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first binder, and then granulating to obtain a core; S2; mixing the deoxidizer, the second adhesive and the core and granulating them to form an intermediate layer on the surface of the core; S3: heating the fat-soluble material to obtain a coating solution, and using the coating solution to coat the material obtained in step S2 to form a coating layer on the surface of the intermediate layer.
9. The method according to claim 8, characterized in that In step S1, the total weight of the modified zero-valent iron, the electron shuttle, the biostimulatory material and the first adhesive is 100 weight %, the content of the modified zero-valent iron is 40-60 weight %, the content of the electron shuttle is 10-20 weight %, the content of the biostimulatory material is 10-40 weight %, and the content of the first adhesive is 5-15 weight %; Preferably, the modified zero-valent iron is selected from one or more of polyethylene glycol-modified zero-valent iron, carboxymethyl cellulose-modified zero-valent iron and sodium oleate-modified zero-valent iron; Preferably, the electron shuttle is selected from sodium anthraquinone-2,6-disulfonate and / or riboflavin; Preferably, the biostimulant material is selected from one or more of yeast extract, nitrogen source and phosphorus source.
10. The method according to claim 8 or 9, characterized in that: In step S1, the particle size of the core is 20-35 μm.
11. The method according to claim 8 or 9, characterized in that: In step S2, the deoxidizing agent is selected from one or more of sodium sulfite, ascorbic acid and glucose oxidase. Preferably, the ratio of the deoxidizer to the second adhesive is 5-8:
1.
12. The method according to claim 8 or 11, characterized in that: In step S2, the ratio of the total weight of the deoxidizer and the second adhesive to the weight of the inner core is 1:2-3.
13. The method according to any one of claims 8 to 12, characterized in that: In step S2, the thickness of the intermediate layer is 5-10 μm.
14. The method according to claim 8, characterized in that The specific process of step S3 includes: The fat-soluble material is heated to obtain a coating liquid, the material obtained in step S2 is placed in a preheated fluidized bed coater, and then the coating liquid is sprayed into the coating machine for coating, followed by drying.
15. The method according to claim 8 or 14, characterized in that In step S3, the volume ratio of the coating liquid to the material obtained in step S2 is 1:2-5.
16. The method according to any one of claims 8 to 15, characterized in that: In step S3, the thickness of the coating layer is 10-20 μm.
17. The method according to any one of claims 8 to 16, characterized in that: In step S3, the fat-soluble material is selected from fatty acids and / or paraffin; Preferably, the fatty acid is selected from C16-C20 fatty acids.
18. A self-identifying and repairing material for heavy non-aqueous pollutants prepared by the method according to any one of claims 8 to 17.
19. Use of the self-identifying and repairing material for heavy non-aqueous phase pollutants according to any one of claims 1 to 7 and 18 in the repair of heavy non-aqueous phase pollutants.
Citation Information
Patent Citations
Method for remediation of soil polluted by high-concentration organic matters
CN106269823A
A compound biological agent and its application in the remediation of polychlorinated biphenyl (PCB) contaminated soil.
CN107586747B
Reducing agent used for in-situ remediation of underground water polluted by chloro-hydrocarbons and preparation and use methods of same
CN109019819A
Technology for repairing non-aqueous phase pollution of underground water
CN111137941A
A compound biological agent for remediating polychlorinated biphenyl (PCB) contaminated soil
CN111235077B